Multi-modality 3D mandibular resection planning in head and neck cancer using CT and MRI data fusion: A clinical series. (June 2018) - Kraeima, J.; Dorgelo, B.; Gulbitti, H.A.; Steenbakkers, R.J.H.M.; Schepman, K.P.; Roodenburg, J.L.N.; Spijkervet, F.K.L.; Schepers, R.H.; Witjes, M.J.H.
Highlights: Integration of CT and MRI data into a 3D virtual model for resection planning. Safe and accurate method for 3D planning of mandibular resections. Multidisciplinary approach including the a new professional: the technical physician. Abstract: Objectives: 3D virtual surgical planning (VSP) and guided surgery has been proven to be an effective tool for resection and reconstruction of the mandible. Currently, most widely used 3D VSP approaches to mandibular resection do not include detailed tumour information in the VSP. This manuscript presents a strategy where the aim was to incorporate tumour visualisation into the 3D virtual plan. Three-dimensional VSP of the mandibular resections was based on the fusion of CT and MRI data which was subsequently applied in clinical practice. Methods: All patients diagnosed with oral squamous cell carcinoma between 2014 and 2017 at the University Medical Centre Groningen were included. The tumour was delineated on the MRI data, after which this dataset was fused with the CT bone data in order to construct a 3D bone and tumour model for virtual resection planning. Guided resections were performed and post-operative evaluation quantified the accuracy of the resection. The histopathological findings and patient and tumour characteristics were compared to those of a historical cohort (2009–2014) of conventional mandibular continuity resections. Results: Twenty-four patients were included in the cohort. The average deviation from planned resection was found to be 2.2 mm. Histopathologic analysis confirmed all resection planes (bone) were tumour free, compared to 96.4% in the historic cohort. Conclusion: MRI-CT base tumour visualisation and 3D resection planning is a safe and accurate method for oncologic resection of the mandible. It is an improvement on the current methods reported for 3D resection planning based solely on CT data.